(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
In this article, in the years of independence, a radical reform of the education sector, the adoption of many laws regulating relations in the field of education, achieving quality and efficiency of education is the main goal of the national education system of any state. The state is analyzed, and this process is a highly continuous development of the material and technical base of educational institutions, improvement of its regulatory framework, educational and methodological support, modernization of management and control of education based on modern pedagogical technologies.